(untitled) - Hamdan, Mahmoud (Hoboken, N.J., 2005)
The last few years have seen an unprecedented drive toward the application of proteomics to resolving challenging biomedical and biochemical tasks. Separation techniques combined with modern mass spectrometry are playing a central role in this drive. This book discusses the increasingly important role of mass spectrometry in proteomic research, and emphasizes recent advances in the existing technology and describes the advantages and pitfalls as well.
Keywords: Proteins,Mass spectrometry,Proteomics,Prô - tê - in,Phép đo phổ khối lượng; Spectra,Quang phổ